Motivation of Japanese language students during pandemic Covid-19 at Universiti Teknologi Mara - Choong, Pow Yean; Ahmad, Normah; Mohd Samsir, Sri Qamariah; Mohd Zin, Zaid; Rosiah, Rosi (Human Resource Management Academic Research Society, 2022)
Motivation is one of the most important stimuli in learning. The COVID-19 pandemic of 2020 has resulted in changes in teaching and learning patterns. A study on the subject was conducted to identify the motivation categories of students and analyze the factors influencing their motivation toward Japanese language learning during the COVID-19 pandemic period. This study is a quantitative study that utilizes a Google Form questionnaire. A total of 366 Japanese language learners answered the questionnaire. Data obtained from the questionnaire were analyzed using the Statistical Package for Social Science (SPSS). The findings showed that although classes were conducted online, Universiti Teknologi MARA (UiTM) students were highly motivated to learn Japanese as a foreign language. The highest motivation was the classroom support category with a very high mean score (M = 4.6), followed by integrative motivation (M = 4.4) and instrumental motivation (M = 3.8). The structure of the Japanese language, culture, and the interesting way of life of the Japanese people have been the factors influencing the motivation to learn the Japanese language. In addition, learning methods and materials, peer interaction, and the positive attitude of lecturers are also important factors that influence the motivation of Japanese language students. In times of the pandemic, classroom support plays a big role in maintaining the motivation for students to study a second language.